Dose-escalated intensity-modulated radiotherapy and irradiation of subventricular zones in relation to tumor control outcomes of patients with glioblastoma multiforme - Kusumawidjaja, Grace (Onco Targets Ther, 2016)
BACKGROUND: Glioblastoma multiforme (GBM) is the most aggressive primary brain tumor with high relapse rate. In this study, we aimed to determine if dose-escalated (DE) radiotherapy improved tumor control and survival in GBM patients. METHODS: We conducted a retrospective analysis of 49 and 23 newly-diagnosed histology-proven GBM patients, treated with DE radiotherapy delivered in 70 Gy (2.33 Gy per fraction) and conventional doses (60 Gy), respectively, between 2007 and 2013. Clinical target volumes for 70 and 60 Gy were defined by 0.5 and 2.0 cm expansion of magnetic resonance imaging T1-gadolinium-enhanced tumor/surgical cavity, respectively. Bilateral subventricular zones (SVZ) were contoured on a co-registered pre-treatment magnetic resonance imaging and planning computed tomography dataset as a 5 mm wide structure along the lateral margins of the lateral ventricles. Survival outcomes of both cohorts were compared using log-rank test. Radiation dose to SVZ in the DE cohort was evaluated. RESULTS: Median follow-up was 13.6 and 15.1 months for the DE- and conventionally-treated cohorts, respectively. Median overall survival (OS) of patients who received DE radiotherapy was 15.2 months (95% confidence interval [CI] =11.0–18.6), while median OS of the latter cohort was 18.4 months (95% CI =12.5–31.4, P=0.253). Univariate analyses of clinical and dosimetric parameters among the DE cohort demonstrated a trend of longer progression-free survival, but not OS, with incremental radiation doses to the ipsilateral SVZ (hazard ratio [HR] =0.95, 95% CI =0.90–1.00, P=0.052) and proportion of ipsilateral SVZ receiving 50 Gy (HR =0.98, 95% CI =0.97–1.00, P=0.017). CONCLUSION: DE radiotherapy did not improve survival in patients with GBM. Incorporation of ipsilateral SVZ as a radiotherapy target volume for patients with GBM requires prospective validation.